Effect of the program "move for your health" on body composition, blood pressure, sleep quality, and academic stress on students in the dormitory building of a confessional private university - Salinas Arias, Saulo Andres (2016)
Adventist institutions promote a healthy lifestyle in the university community as part of compliance with the health reform. Goal: To determine the efficiency of the program "Move for your health" on body composition, blood pressure, sleep quality, and academic stress on students living in the dorms at UPeU Tarapoto, Peru. Methodology: To carry out the physical activity program called "Move for your health" with 79 students (Female 59 – Male 20) between the ages of 16 and 19 who live on campus. The variables considered were: body composition (IMC-P.ABD), blood pressure (S-D), sleep quality (PQSI), and academic stress (SISCO). The study design was pre experimental with pre and post test. Data analysis was using SPSS (20.0) statistical software. The descriptive analysis of the sociodemographic characteristics and the student's t-test for related samples. Results: The differences in median pre and post BMI and P.ABD are minimal. In the PA, PSQI, and SISCO are wide. In the t-test for related samples, pre and post test, we see that on IMC and P.ABD of FCS and FIA there are no statistically significant differences except the P.ABD of FCE with p = .033. Finally, in the three departments, the variables PAS-D, show statistically significant differences, with p <0.05. and the PSQI and SISCO the FIA, no different. Conclusions: The physical-activity program developed had a significant effect on the PA, PSQI, and SISCO; however, we did not get expected results for IMC and P.ABD